On the Interplay Between Chirality and Exciton Coupling: A DFT Calculation of the Circular Dichroism in π‐Stacked Ethylene. Issue 9 (19th May 2014) - Norman, Patrick; Linares, Mathieu
ABSTRACT The chirality of stacked weakly interacting π‐systems was interpreted in terms of Frenkel exciton states and the formation of excitonic circular dichroism (CD) bands was monitored for ethylene stacks of varying sizes. Convergence of CD bands with respect to the system size was observed for stacks involving around 10 molecules. By means of rotation around the C–C double bond in ethylene, chirality was induced in the monomeric system and which was shown to dominate the spectral responses, even for polymer aggregates. In helical assemblies of chiral entities, there will always be a mix of excitonic and monomeric contributions to the CD signal and it is demonstrated that the complex polarization propagator approach in combination with Density Functional Theory is a suitable method to address this situation. Chirality 26:123–129, 2014. © 2014 Wiley Periodicals, Inc.